Theory of Differential Algebraic Equations: Structural Study and Numerical Solution: A Geometric Approach to Analyzing and Solving Polynomial Differential-Algebraic Equations (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the most recent two decades differential-algebraic equations (DAEs) have turned into a significant limb in numerical examination. In this Paper we concentrate on them from another, geometric perspective. The DAE is translated as a subset of a plane cluster and its answer are actuated by the Cartan dissemination on the plane bunch. We additionally acquaint a technique with look at and demarcate the structure of a general, polynomial, DAE whose locus is possibly a fibred complex. Likewise it is indicated how a few singularities of multibody frameworks are uprooted by utilizing the algebraic strategies utilized as a part of this methodology.